The dynamics of male harem dominance in southern elephant seals (Mirounga leonina) at the South Shetland Islands - Carlini, Alejandro R.; Poljak, Sebastián; Daneri, Gustavo A.; Márquez, María E. I.; Negrete, Javier (Polar biology, 2006)
Breeding chronology, harem structure and changes in male harem dominance were studied at Stranger Point, Isla 25 de Mayo/King George Island, principally by extensive field census work during the 2003 breeding season. Males were individually identified and their size estimated by using a photogrammetric method. Peak female haul out for the population occurred on 31 October, when a total of 276 females were observed along 7 km of coastline, distributed in ten harems with a median size of 16 females. Overall sex ratio and harem sex ratio for the breeding population were 1:6.7 and 1:10.6, respectively. A total of 33 males were identified associated with harems. Male size conferred an advantage in terms of dominance hierarchy, since dominant males (4.91±0.15 m) were significantly longer than subordinate males (4.63±0.19 m). Harems were dominated by an average of 4.5 (range 2-7) different males during the breeding season. Elephant seals at Stranger Point breed in very low density aggregations. The main breeding events in this population occurred later than at other breeding sites, which agrees with previous observations in the area. Male movement among harems suggests that differences in mating success among males could be achieved through their different behaviours.[PUBLICATION ABSTRACT]